Faktor-Faktor yang Berperan pada Literasi Keuangan Mahasiswa Muslim di Kota Serang - Ibrohim Ibrohim; Leni Triana; Rina Nopianti (Owner : Riset dan Jurnal Akuntansi, 2022)
Various financial literacy education programs are organized by the Financial Services Authority to improve public financial literacy. Students and university students in general are the main focus of financial education efforts aimed at educating the general public. College students are one of the priority targets of the Indonesian Financial Services Authority's (OJK) financial education programs in Indonesia. The purpose of this study was to (1) assess the level of Islamic financial literacy among Serang college students and (2) investigate the factors that influence their level of Islamic financial literacy. The score of Islamic financial literacy was used as the independent variable in this study. The dependent variables are gender, university, Grade Point Average (GPA), information sources, and religiosity. The descriptive analysis and structural equation modeling partial least squares are used to analyze the data (SEM-PLS). According to the estimation results, the level of Islamic financial literacy among Muslim students in Serang is 50.2 percent, which is classified as sufficient literate. Gender and university were found to have a positive and significant influence on the level of Islamic financial literacy of Muslim students in Serang, according to the study.